INTENSITY OF INFECTION WITH STRONGYLIDS NEMATODES IN HORSES FROM SOUTHEAST MEXICO - González-Garduño, Roberto; Nuncio-Ochoa, María Guadalupe J.; Navarro-Martínez, Fernando; Arroyo Balán, Fabián; Arias Vázquez, María Sol; Paz-Silva, Adolfo (Chilean Journal of Agricultural & Animal Sciences, 2015)
A coprological study was conducted to determine the intensity of infection with gastrointestinal nematodes (GIN) in horses, and the influence of climatic conditions on the reinfection of the animals. To determine intensity of infection, samples of faeces were collected in horses from Tabasco and Chiapas, Mexico. In the second study, 20 horses were treated with fenbendazole (7.5 mg kg-1 body weight, BW) at the beginning of each season. The samples were processed by the McMaster te chnique to estimate the number of eggs per gram of faeces (EPG), and coprocultures were performed to identify the main genres and species of strongylids. Several intrinsic factors (age, gender), the origin of animals (state and locality) and season over the level of infection of animals were studied. The main species identified were: Strongylus equinus, S. edentatus, S. vulgaris, Trichostongylus spp., and also larvae were classified as Cyathostominae. Results showed that 86% of the horses tested positive for strongylids. Intensity of infection reached 1182 ± 131 EPG on average. The FEC were higher in adult horses (1093 ± 143 EPG) than in young and old horses (829 and 936 EPG, respectively). Values above 1000 EPG were observed two months after the application of anthelmintic in the three seasons (cold (Norths), dry and rainy). It was concluded that reinfection by strongylids is high in horses, especially by Cyathostominae, throughout the year in warm humid climates of the southeast of Mexico